2019
DOI: 10.1097/bot.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Malnutrition Are Associated With Inpatient Postoperative Complications and Mortality in Hip Fracture Patients

Abstract: Objective: To examine the relationship of nutrition parameters with the modified frailty index (mFI) and postoperative complications in hip fracture patients. Design: Retrospective observational cohort study. Setting: Urban, American College of Surgeons–Verified, Level-1, Trauma Center. Patients/Participants: Three hundred seventy-seven consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…Although preoperatively there were no significant connections between malnutrition and postoperative complication, 6-8 weeks after surgery there were strong correlations towards the MNA status and the NRS status. This shows a major influence of clinical parameters and malnutrition on the postoperative complications and rehabilitation [51]. Both scores are frequently used with geriatric patients.…”
Section: Clinical Correlations To Postoperative Complications and Mormentioning
confidence: 99%
See 1 more Smart Citation
“…Although preoperatively there were no significant connections between malnutrition and postoperative complication, 6-8 weeks after surgery there were strong correlations towards the MNA status and the NRS status. This shows a major influence of clinical parameters and malnutrition on the postoperative complications and rehabilitation [51]. Both scores are frequently used with geriatric patients.…”
Section: Clinical Correlations To Postoperative Complications and Mormentioning
confidence: 99%
“…The mobility upon discharge has a major impact on postoperative survival. Preoperative improvements on these basic clinical parameters as well as supporting postoperative mobility and self-sufficiency significantly reduces postoperative mortality [45,51]. Limited access to daily nutrition, impaired mobility and dependent living conditions prior to surgery facilitate postoperative mortality within 6-8 weeks after surgery.…”
Section: Clinical Correlations To Postoperative Complications and Mormentioning
confidence: 99%
“…Thirteen cohort studies reported on the prevalence of malnutrition in severely injured trauma patients ( Table 1). The prevalence of malnutrition ranged from 7 to 76% in trauma patients in general [10,[25][26][27][28][29][30][31][32][34][35][36]. Six studies specifically reported the prevalence of malnutrition on geriatric patients admitted with traumatic injuries.…”
Section: Prevalence Of Malnutrition and Its Association With Patient mentioning
confidence: 99%
“…Six studies specifically reported the prevalence of malnutrition on geriatric patients admitted with traumatic injuries. On admission, 7-62.6% of the geriatric trauma patients were malnourished and 35.6-60% were at risk for malnutrition according to the Mini Nutritional Assessment (MNA) tool, Nutritional Risk Screening (NRS 2002) tool and serum biomarkers (visceral proteins) [26,27,29,30,35,36]. Dhandapani et al also examined the development of malnutrition during hospital stay and showed an increase in prevalence from 45% in the first week of hospital admission to 76% in the third week [25].…”
Section: Prevalence Of Malnutrition and Its Association With Patient mentioning
confidence: 99%
“…Since this time, it has become clear that malnutrition in patients who are undergoing major surgery are at considerable risk for increased mortality and morbidity . A multitude of research highlights the risk of postoperative complications in malnourished patients undergoing orthopedic procedures, colorectal surgery, bariatric surgery, and other major surgery…”
Section: Trauma and Surgical Patient Populationmentioning
confidence: 99%